Filsafat Eksistensialisme Ali Syariati Dalam Posisi Manusia Beragama di Era Milenial - Shabrina; Nasution, Hasnah (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
Technological developments and social dynamics in the millennial era have brought significant changes to the way humans understand their existence and religiosity. This condition poses new challenges, especially in maintaining the meaning of life, freedom, and the responsibilities of religious humans amid the tide of digitalization. This study aims to analyze Ali Syariati's philosophy of existentialism in explaining the position of religious humans in the millennial era. The research method used is qualitative with a descriptive-analytical approach through philosophical studies. Data were obtained from literature studies covering Ali Syariati's major works and supporting literature in the form of relevant books and scientific articles. Data analysis techniques were carried out by interpreting key concepts in Ali Syariati's thinking, such as basyar, insan, freedom, and responsibility, and then relating them to the phenomenon of religiosity among the millennial generation. The results of the study show that Ali Syariati's existentialism emphasizes humans as beings who continue to progress towards awareness and perfection through responsible freedom. The conclusion of this study affirms that Ali Syariati's thinking is relevant as a reflective framework for religious people in the millennial era and has implications for strengthening critical, contextual, and meaningful religious awareness.